Generating and protecting business ideas understanding business studies - Taylor, Steve; Video Education Australasia (United Kingdom : Video Education Australasia, 2010)
In business, a good idea can be worth millions. But how do you generate and then protect crucial ideas effectively from competitors? In this excellent program we explore how businesses develop and protect business ideas. Split into three defined sections and including input from new and established entrepreneurs including Philip Taylor, Sir James Dyson and leading patent lawyer Carin Burchill, this program looks at sources and development of business ideas, spotting trends and finding a niche market, copyright, patents and trademarks.
Narrator: Steve Taylor.
DVD format
Keywords: Business planning; Intellectual property -- Great Britain; Business enterprises; Business ethics